Response of Chicken that Having Experience Infection of Ascaridia galli to Re-infection and itâs Implication to Productivity and Quality of Eggs - Zalizar, L; Satrija, F; Tiuria, R; Astuti, DA (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2007)
The aimed of this research was to find out the effect of infection experience of Ascaridia galli on productivity and eggs qualities. The research was held in Helminthology Laboratory, Veterinary Faculty and Animal Production Laboratory, Faculty of Animal Husbandry, Bogor Institute of Agriculture. The research was based on a Randomized Completely Design. Â The treatments were P0 = without infection ; P1 = have been infected with Â 200 infectiveÂ eggs A. galli every chick every week ( 8, 15, 22 and 30 days old chick) and re-infected with 500 infected eggs at 18 weeks old; P2= chicks withÂ no infection experience at starter period, and infected with 500 infected eggs at laying period. The productivity and quality of eggs were examined. The results showed that infection experience of Ascaridia galli influenced the layer productivity and their eggs qualities. The experience of A. galli infection several times with light dosage at starter period (P1) made the layers more resistance to re-infection by the parasite in the laying period. Consumption and conversion of feed, eggs weight, shell thickness and calcium concentration of P1 was not significant difference with control group (P0). First A. galli infection in layer period in group without experience of A. galli infection before (P2), have showed that, compare with the control group (P0), the feed conversion of P2 was 15.78% higher (P<0.01), eggs weight of P2 was lighter 5.35% (P<0.05), the shell thickness of P2 eggs was lower 5.55% (P<0.05), the calcium concentration in serum was lower 36.26% (P<0.05). Beside that the color of eggs yolk in infected (P1 and P2) group more colorless (11.63%) than control group. A. galli (P<0.01). Ascaridia galli infection has no effects on Haugh Unit Value, titer serum protein and eggs protein. (Animal Production 9(2): 92-98 (2007)Â Key Words : Infection experience, Ascaridia galli, productivity of layer, eggs qualities